ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMILIH HANDPHONE - Hayun, Anggara; Sundari, Sundari (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
The research discusses the influencing factors for customers in choosinghandphone. Todays globalization era causes handphones as a primary needs for people. New Innovation of handpone technology is created to attract customers interested by handphone industries. However, to attract customers interested to use it, handphone industries need to consider some factors that influence customers in choosing handphone. The result shows some factors that influence the customers in choosing handphone are design, feature, and price.